A brief account of the history of family planning in Costa Rica - Carranza Maxera, María (2009)
Costa Rica has been a focus of demographic attention for at least two reasons: its startling rate of natural population growth, which peaked at 3.8% during 1955 and 1960 and which was considered one of the highest in the world3; and the astounding decline in the total fertility rate, from 7.3 to 3.7 children, that took place between 1960 and 1975, and which has rarely been recorded elsewhere (Gómez, 1968: 3; Reynolds, 1973: 312; Rosero-Bixby, 1979: 4). This sharp reduction in the fertility rate, which occurred in all strata of the population, albeit with varying intensity and chronology4, has been attributed in large measure to the use of modern contraceptive methods (Rosero-Bixby, 1979:13; 1986: 70-71). Their provision by state health institutions played a fundamental role in accelerating the phenomenon and spreading it from urban and educated women (among whom it started) to rural and less educated women (Rosero-Bixby, 1986: 70-71).